The implementation of sustainability practices in portuguese higher education institutions - Aleixo, Ana Marta (2018)
The purpose of this work is to analyze the current state of implementation of sustainability development (SD) in Portuguese higher education institutions (HEIs). Design/methodology/approach A questionnaire was developed to measure the level of implementation of SD practices in HEIs as well as the number of rankings, certifications and declarations of these institutions. The questionnaire was sent by e-mail to all rectors, presidents, directors of faculties, departments and schools of Portuguese universities and polytechnics. A sample of 53 leaders was obtained. Findings Portuguese HEIs are mainly engaged in the social dimension of sustainability. The economic dimension emerges in second place and the institutional in third; the environmental dimension is the least developed. Except for a few specific topics (e.g. related to research on SD, and the offer of degree courses in SD), there are no significant differences between universities and polytechnics in the implementation of SD practices. Only 11 per cent of HEIs are innovators in the implementation of SD practices, and a majority of HEIs have implemented less than 34 per cent of the SD practices studied. Research limitations/implications This research has a national scope, and the results should be interpreted only in the Portuguese context. Future studies should include a larger range of institutional actors within the faculty. Practical implications This study provides valuable insights and theoretical and methodological guidance for future implementation processes supporting the transition to sustainability in HEIs. Originality/value This is the first study conducted in Portuguese HEIs with the aim of determining their efforts to implement and promote sustainability.